2020
DOI: 10.1101/2020.03.23.004093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and behavioral adaptation ofCandida parapsilosisto the microbiome of hospitalized infants revealed byin situgenomics, transcriptomics and proteomics

Abstract: Candida parapsilosis is a common cause of invasive candidiasis, especially in newborn infants, and infections have been increasing over the past two decades. C. parapsilosis has been primarily studied in pure culture, leaving gaps in understanding of its function in microbiome context. Here, we reconstructed five unique C. parapsilosis genomes from premature infant fecal samples and analyzed their genome structure, population diversity and in situ activity relative to reference strains in pure culture. All fiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In 2020, we found that the RTA3 gene has undergone amplification in 23 clinical isolates of Candida parapsilosis, resulting in increased copy number of 24-33x [42]. Variable copy numbers of RTA3 were also found by West et al [43] in four isolates. Here, by genome sequencing, we report that RTA3 amplification is very common in C. parapsilosis.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…In 2020, we found that the RTA3 gene has undergone amplification in 23 clinical isolates of Candida parapsilosis, resulting in increased copy number of 24-33x [42]. Variable copy numbers of RTA3 were also found by West et al [43] in four isolates. Here, by genome sequencing, we report that RTA3 amplification is very common in C. parapsilosis.…”
Section: Introductionmentioning
confidence: 61%
“…We also found that there have been multiple independent events of amplification, with at least 16 unique endpoints. West et al (2021) previously described RTA3 amplifications in 4 C. parapsilosis isolates, including one from the New York subway [43]. Those amplifications also have different endpoints, but because the data comes from metagenomics analyses, we cannot determine if their endpoints differ from the 16 CNVs we describe.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…CPAR2_301940 ). C. parapsilosis is on average less heterozygous than C. albicans (0.1-0.4 SNP/kb versus 3 SNP/kb, respectively) (34, 35). To maximize the chances of detecting LOH, we selected strains in which the target gene was followed by regions containing at least some heterozygous sites.…”
Section: Resultsmentioning
confidence: 99%